IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DAN PROFIL PELAJAR RAHMATAN LIL ALAMIN (PPRA) TEMA KEARIFAN LOKAL - Elma Kumala; Ida Fauziatun Nisa’; Usman Roin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
Education serves as a method of passing down cultural legacy, knowledge, and abilities to the following generation. The curriculum is a vital instrument in achieving educational objectives. "Curriculum Merdeka" is a new program introduced by the Indonesian government with the aim of creating a more contextual curriculum for all students in Indonesia. In this context, project-based learning is utilized to strengthen students' profiles in Pancasila and Rahmatan Lil Alamin. This study aims to comprehend the implementation process and the factors that facilitate and impede it factors in executing the P5-PPRA theme of local wisdom at MTs Roudloh. This research employs qualitative methods. The findings reveal several stages in implementing P5-PPRA at MTs Roudloh Semambung. The planning stage involves forming a facilitation team, evaluating the madrasah's preparedness, choosing the project's scope, themes, and duration, and creating project modules. The beginning, context, action, introspection, and follow-up are all included in the implementation stage. The assessment stage involves assessing the implementation of P5-PPRA based on observations. Supporting factors include the enthusiasm and eagerness of students, sufficient infrastructure and facilities, as well as the school's support environment. Hindering Among the factors are teachers' limited understanding of The updated curriculum and variations in the traits of the students. In conclusion, the implementation of P5-PPRA has been conducted effectively in accordance with the guidelines, despite being in its initial stages